PP044 Adherence To Enzyme Replacement Therapy In Gaucher Disease. (2017) - Quevedo, Amanda; Dornelles, Alicia; Paskulin, Livia; Alegra, Taciane; Krug, Barbara; Vairo, Filippo; Picon, Rafael; Shwartz, Ida; Picon, Paulo
Abstract : INTRODUCTION: Gaucher disease (GD) is a genetic autosomic disorder for which treatment has been funded by the Brazilian government since the 1990s. In our state most patients are treated with enzyme replacement therapy (ERT) and followed by our Reference Center under the recommendation of the Ministry of Health Brazilian guidelines. There is a lack in the literature about adherence of patients to treatment. The objective was to describe adherence to the treatment in a cohort of all GD patients in the southern state of Brazil. METHODS: This was a cohort study of all GD patients treated with velaglucerase α, taliglucerase α and imiglucerase from January 2010 to January 2015. Adherence was measured as recommended by the Brazilian guidelines as to perform more than 50 percent of the anticipated infusions per year. RESULTS: Our study included thirty-seven patients of both genders. Doses of ERT varied from 15 to 45IU/kg for type 1 patients and from 30 to 60 IU/kg for type 3 patients. A mean of 83 percent of anticipated infusions were performed and from all patients only one did not adhere to the treatment during the 5 years of our study. The majority of the patients performed at least 50 percent of all anticipated infusions. CONCLUSIONS: We noted a very high rate of adherence to treatment with a very few adverse effects. Our data might be showing that the very high rate of adherence in these chronic disease patients may be attributed to the value of treatment by patients and their family, and also due to the existence of a multidisciplinary team at the reference center. These data might be useful for public health policy making in other countries.